Civil War battles [ - McNeese, Tim (New York : Chelsea House Publisher, 2009)
A look at the various battles of the Civil War.
Bull Run (Manassas) -- Shiloh -- The Seven Days -- Antietam (Sharpsburg) -- Fredericksburg -- Chancellorsville -- Gettysburg -- Chattanooga -- Spotsylvanie.
Description based on print version record
Includes bibliographical references (p 132-133) and index
Keywords: United States -- History -- Civil War, 1861-1865 -- Campaigns